Peran Guru dalam Mengimplementasikan Kurikulum 2013 di Sekolah - Neliwati Neliwati; Inda Lestari; M. Khalid Pay Hasibuan; Syarifah Tussuriyani Hasibuan (Departement of Mathematics Education, 2024)
The 2013 curriculum is a pedagogical framework that aims to improve the quality of education in Indonesia by emphasizing the development of students' character, skills and knowledge. The role of teachers in implementing the 2013 Curriculum in schools is crucial in ensuring the success of providing education in accordance with the objectives of the curriculum. This study aims to investigate the role of teachers in the process of implementing the 2013 Curriculum in schools. Qualitative research methods were used by conducting in-depth interviews with a number of teachers in various schools. The results of the analysis show that the teacher's role in implementing the 2013 Curriculum involves several main aspects. However, there are challenges faced by teachers in implementing the 2013 Curriculum, such as limited resources, uneven understanding of the new curriculum, and paradigm changes in learning approaches. Further efforts are needed to support teachers in carrying out their role effectively in implementing the 2013 Curriculum, including more intensive training, strong leadership support at the school level, as well as increasing available resources.